American Treasuries yield curve construction and its forecast with application in trading - Karmadonov, Savva (2024)
This thesis explores the construction of the American Treasuries yield curve and its implications for financial trading. The yield curve, a key financial indicator, reflects market expectations for economic growth, inflation, and future interest rates. By analyzing the American Treasuries yield curve, this study aims to provide insights into term structure modeling, with a particular focus on comparing models that incorporate macroeconomic variables against those that do not. The research evaluates various methodologies, including interpolation methods and stochastic interest rate models, concentrating on parametric interest rate models, and examines their effectiveness in forecasting yield curve movements. Additionally, the study applies these forecasts to trading strategies, demonstrating their practical applications. The findings contribute to the understanding of yield curve dynamics and offer valuable tools for traders navigating the complexities of financial markets.